2018
DOI: 10.26522/ssj.v12i2.1626
|View full text |Cite
|
Sign up to set email alerts
|

From Schoolgirls to “Virtuous” Khmer Women: Interrogating Chbab Srey and Gender in Cambodian Education Policy

Abstract: Chbab Srey (Code of Conduct for Women) is an important piece of Khmer literature outlining expected behavior for girls and women in Cambodia. Pieces of the poem are taught in secondary school and interwoven into the educational experiences of girls and female teachers, yet there is little research on Chbab Srey in education. Using discourse analysis, this article considers the influence of Chbab Srey on gender-related education policy in Cambodia. This research highlights the juxtaposition of Chbab Srey and ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…Interestingly, this result is in line with Anderson and Grace (2018)'s study which revealed how Cambodian girls and women were ideologically constructed to be 'ladylike' and 'honest' with their husbands. To be more specific, the authors investigated Cambodian education policy, using policy discourse analysis as a tool, and found that this education policy used a poem Chbab Srey (Code of Conduct for Women) to be taught in secondary schools.…”
Section: Collocates Of Lady (กุ ลสตรี ) and Ethics (จริ ยธรรม) With MI Scoressupporting
confidence: 84%
“…Interestingly, this result is in line with Anderson and Grace (2018)'s study which revealed how Cambodian girls and women were ideologically constructed to be 'ladylike' and 'honest' with their husbands. To be more specific, the authors investigated Cambodian education policy, using policy discourse analysis as a tool, and found that this education policy used a poem Chbab Srey (Code of Conduct for Women) to be taught in secondary schools.…”
Section: Collocates Of Lady (กุ ลสตรี ) and Ethics (จริ ยธรรม) With MI Scoressupporting
confidence: 84%
“…Indeed, women's land rights and customary law exist in parallel to social norms that constrain women's power and rights in the family, community, and society. These are outlined in the chbab srey (' women's code'), a poem originating in the 19th century, which is widely memorized and reproduced in school curricula ( see Anderson and Grace, 2018). It constructs the notion of the ' perfectly virtuous woman' ( srey kruap leak), subordinate to men and obeying them irrespective of their demands or behaviour, including violence ( Lilja, 2008, 70-71).…”
Section: Political and Gender Orders In A Hybrid Statementioning
confidence: 99%
“…Historical texts that describe appropriate codes of social conduct still circulate widely in Cambodian schools and have significant cultural value and meaning in wider society (Brickell, 2016;Anderson and Grace, 2018). Within these behavioral "rulebooks, " women are expected to maintain a harmonious household, including financial management, raising children, and performing domestic work, as well as engaging in trade and crop production; while men are tasked with protection and governance (Ledgerwood, 1996;Brickell and Springer, 2016).…”
Section: Gender Dynamics In Rural Cambodiamentioning
confidence: 99%